Komisi Pemberantasan Korupsi Wiretapping Authority After The Revision Of Law Number 19 Year 2019 Regarding The Corruption Eradication Commission - Fahririn, Fahririn (Veteran Law Review, 2020)
The formation of Dewan Pengaawa is also very necessary considering that every agency needs a controller when carrying out its duties and authorities. The formation of Dewas is expected to provide clear and measurable boundaries related to the implementation mechanism and the work system of state institutions. The presence of Dewas later expected to work professionally considering Dewas's task in the revision of the KPK Law, in addition to supervising the KPK's performance as well as wiretapping permits The application of wiretapping as one of the investigative and investigative authorities has helped many legal processes, but tapping does need to be regulated and supervised in order to reduce and prevent abuse of authority. Moreover, the KPK Law has been in effect for 17 years, so it requires adjustments and arrangements for matters that are not yet clear in the KPK Law. For example, related to wiretapping by the KPK which has never been audited by Kominfo since 2009. This is an impact of the Constitutional Court Decision No. 5 / PUU-VIII / 2010 which states that tapping cannot only be regulated by a ministerial regulation but must be regulated by law